Depression prevention in adolescents based on Buddhism and Sufficiency Economy Philosophy - Kwaunpanomporn Thummathai (2020)
© 2019 Elsevier Inc. Depression among young adolescents can affect the learning performance and quality of life, and increase suicidal risk. Depression prevention (DP) intervention at the early onset is thus important. The participants were 20 adolescents aged between 10 and 14, 5 parents, and 7 teachers who resided in the same province in northern Thailand. Descriptive statistics were employed for data analysis, while qualitative data from four focus group discussions (FGDs) and 17 in-depth interviews (IDIs) were analyzed through content analysis. The findings revealed that the critical component of depression prevention model for adolescents is self-worth enhancement, which comprises of the enhancement of self-esteem, problem-solving skills, and relaxation based on Buddhism and Sufficiency Economy Philosophy (SEP) for emotional balancing in order to prevent depression in adolescents.